2016
DOI: 10.1038/srep22861
|View full text |Cite
|
Sign up to set email alerts
|

Testis-specific serine/threonine protein kinase 4 (Tssk4) phosphorylates Odf2 at Ser-76

Abstract: As a member of the testis-specific serine/threonine protein kinase (TSSK) family, Tssk4 is exclusively expressed in the testis and plays an essential role in male fertility. We previously reported that Tssk4 can associate with and phosphorylate Odf2, but the phosphorylation site is still unknown. Here we confirm that the C-terminal region (amino acids 214-638) of Odf2 is required for association with Tssk4. Furthermore, to identify the site at which Tssk4 phosphorylates Odf2, we generated several Odf2 point mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…6h). Furthermore, TSSK4 was reported to influence sperm flagellar formation by enhancing the phosphorylation state of ODF2, which is a prominent protein of the sperm tail outer dense fibers 13,3033 . Because no commercial antibody was available, we did not confirm that TSSK4 can increase the phosphorylation of ODF2.…”
Section: Resultsmentioning
confidence: 99%
“…6h). Furthermore, TSSK4 was reported to influence sperm flagellar formation by enhancing the phosphorylation state of ODF2, which is a prominent protein of the sperm tail outer dense fibers 13,3033 . Because no commercial antibody was available, we did not confirm that TSSK4 can increase the phosphorylation of ODF2.…”
Section: Resultsmentioning
confidence: 99%
“…Using a yeast two-hybrid approach with the cAMP response element-binding protein (CREB; previously known as AMP-responsive transcription factor) as bait, Chen and coworkers found that TSSK4 can phosphorylate CREB and may stimulate the CRE/CREB pathway by phosphorylation of CREB at Ser-133 [ 31 ]. More recently, TSSK4 was proposed as one of the kinases involved in phosphorylation of outer dense fiber 2 (Odf2), an essential protein in the sperm flagellum [ 56 ]. Using a phospho-specific antibody, in vitro phosphorylation of Odf2 in Ser76 by Tssk4 was verified by co-transfection of Tssk4 and Odf2 serine/tyrosine/lysine-to-alanine point mutants in 293 T cells.…”
Section: In Vitro Biochemical Characterization Of Tssk Kinasesmentioning
confidence: 99%
“…As described above, further experimentation showed that Tssk4 and Odf2, a major cytoskeletal protein, are both localized in the principal piece of the sperm flagellum; it should be noted that Tssk4–Odf2 co-immunolocalization studies could not be performed because both antibodies were raised in rabbits. Based on the similar patterns of distribution in sperm flagellum, it was proposed that Tssk4 and Odf2 could interact in vivo, probably affecting the phosphorylation status of one another [ 56 ], which would in turn explain the abnormal morphology and functionality of sperm flagellum observed in the Tssk4 knockout mice.…”
Section: In Vivo Analysis Of Tssk Kinases By Knockout Mouse Modelsmentioning
confidence: 99%
“…A subsequent literature research revealed that TSSK4 and ATP10D have not been implicated in pathways related to kidney development to date. TSSK4 appears to have a rather specialized role for male fertility [ 28 ] while sequence variants in ATP10D have been demonstrated to significantly associate with metabolic disorders including insulin resistance [ 29 ]. NELL2 and TTLL12 however, remotely appear connected to pathways that have been previously discussed in the development of CAKUT.…”
Section: Resultsmentioning
confidence: 99%